2022
DOI: 10.3389/fmicb.2022.880484
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Secretory Immunoglobulin A in Host-Microbiota Interactions in the Gut Ecosystem

Abstract: In the gastrointestinal tract (GIT), the immune system interacts with a variety of microorganisms, including pathogens as well as beneficial symbionts that perform important physiological functions for the host and are crucial to sustain intestinal homeostasis. In normal conditions, secretory immunoglobulin A (SIgA) is the principal antibody produced by B cells in the GIT mucosa. Polyreactivity provides certain SIgA molecules with the ability of binding different antigens in the bacterial surface, such as O-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 123 publications
1
27
0
Order By: Relevance
“…However, different bacteria induce IgA production at different levels, and also seem to interact with this antibody in different ways. IgA has the capacity to engage in a variety of asymmetrical interactions with different bacterial types, potentially contributing to promoting the retention of habitual gut symbionts while ensuring containment or clearance of opportunistic pathogens [ 66 ]. For instance, interactions between IgA N-glycans and peptidoglycans in the cell wall envelope of beneficial Gram-positive species of the Firmicutes and Actinobacteria appear to favor their retention in the intestine.…”
Section: Implications Of Early Gut Microbiota Colonization For Long-t...mentioning
confidence: 99%
“…However, different bacteria induce IgA production at different levels, and also seem to interact with this antibody in different ways. IgA has the capacity to engage in a variety of asymmetrical interactions with different bacterial types, potentially contributing to promoting the retention of habitual gut symbionts while ensuring containment or clearance of opportunistic pathogens [ 66 ]. For instance, interactions between IgA N-glycans and peptidoglycans in the cell wall envelope of beneficial Gram-positive species of the Firmicutes and Actinobacteria appear to favor their retention in the intestine.…”
Section: Implications Of Early Gut Microbiota Colonization For Long-t...mentioning
confidence: 99%
“…The main function of sIgA, referred to as immune exclusion, is to limit the access of pathogens and food allergens to the mucosal barrier, and thus prevents their spread to the systemic compartment [ 82 ]. In addition, it regulates the balance of gut microbes by favoring the maintenance of beneficial members and the removal of opportunistic pathogens, which in turn prevents the absorption of pathogens and toxins [ 83 , 84 ]. There is evidence that mucosal secretion of sIgA is partially controlled by the gut microbiome and even that specific microbial species can induce its production to a different extent [ 84 ].…”
Section: The Role Of the Gut Microbiome In The Development Of Famentioning
confidence: 99%
“…In addition, it regulates the balance of gut microbes by favoring the maintenance of beneficial members and the removal of opportunistic pathogens, which in turn prevents the absorption of pathogens and toxins [ 83 , 84 ]. There is evidence that mucosal secretion of sIgA is partially controlled by the gut microbiome and even that specific microbial species can induce its production to a different extent [ 84 ]. As a result, the composition of gut microbes strongly influences sIgA production and, consequently, the development of oral tolerance.…”
Section: The Role Of the Gut Microbiome In The Development Of Famentioning
confidence: 99%
“…Yang et al [ 69 ] found that intestinal sIgA production was reduced in NAFLD/NASH rats, suggesting that IgA had a potential function in liver disease. There were other reports that sIgA helped to protect beneficial members of GM and had a special coating ability for Gram-negative bacteria to prevent them from adhering to the intestinal wall, thereby exerting a protective function on the intestinal barrier [ 70 , 71 ]. Conversely, when the intestinal mucosa is damaged, the number of sIgA plasma cells decreases, which may aggravate intestinal bacterial translocation [ 72 ].…”
Section: The Pathogenesis Of Nafld Based On the Gut–liver Axismentioning
confidence: 99%